Temporomandibular joint’s and mandible reconstruction after segmental mandibulectomy in oncological practice - M. A. Kropotov; O. A. Saprina; V. Z. Dobrokhotova; A. D. Shturma (Опухоли головы и шеи)
Introduction. Segmental mandibulectomy with exarticulation and single-step reconstruction is an important problem of craniomaxillofacial surgery. Revascularized autotransplants (iliac crest, fibula free flaps) are used to reconstruct defects of the mandible and restore joint function.Aim. To evaluate functional, esthetic and oncological results of fragmental mandibular resection with exarticulation and single-step reconstruction using bone flaps.Materials and methods. The study included 52 patients who underwent segmental mandibular resection with exarticulation and single-step reconstruction using bone flaps. For defects of the ramus and head of the mandible, reconstruction was performed using iliac crest free flap (5 cases); defects of the ramus and body of the mandible, fibula free flap was used (47 cases).Results. Total necrosis of the flap was observed in 1 (4.7 %) case. Iliac crest free flap was modelled taking into account the size of mandibular ramus defect (usually to the angle of the mandible), mandibular head was formed from the distal part. At least one osteotomy was preformed on the autotrasplant near the angle, on the distal part the head was formed. Follow-up period varied between 1 and 5 years. Disease progression in the form of recurrence was observed in 15 (34.9 %) cases, in the form of distant metastases in 6 (13.9 %) cases.Conclusion. For small defects of the ramus of the mandible, revascularized iliac crest free flap should be used, for large defects the method of choice is fibula free flap. Temporomandibular joint can be formed from the distal end of a bone autotransplant with its subsequent adaptation during functional load.